View from a window - Alt, Jakob, 1789-1872 (artist):::Creator:::::::::::: (2020)
Reproduction of a watercolor painting located at the Belvedere in Vienna with a view of through a window of a building in the Alservorstadt at the Dornbach and the foothills of the Wienerwald.